2005
DOI: 10.1002/qua.20674
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the structures and properties of cyclic nitramines: Tetranitrotetraazadecalin (TNAD) and its isomers

Abstract: Density Functional Theory (DFT) was employed to study the geometries, electronic structures, infrared vibrational spectra, and thermodynamic properties of seven isomeric cyclic nitramines of C 6 H 10 N 8 O 8 (i.e., TNAD and its six isomers) at the B3LYP/6-31G* level of theory. The experimental results available for TNAD were used to determine the reliability of the DFT method for generating structural and IR spectroscopic values for these molecular systems. The relative stabilities of the conformers were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Subsequently, D and P are calculated. It was found that this method is efficient and convenient [17][18][19][20]22]. Studies have indicated that when the average molar volume V estimated by Monte-Carlo method based on 0.001electrons/bohr 3 density space at the B3LYP/6-31G** or 6-31G* level is used, the theoretical molecular density mol ( mol ϭ M/V, M is the molecular weight) is very close to the experimental crystal density cry .…”
Section: Methodsmentioning
confidence: 96%
“…Subsequently, D and P are calculated. It was found that this method is efficient and convenient [17][18][19][20]22]. Studies have indicated that when the average molar volume V estimated by Monte-Carlo method based on 0.001electrons/bohr 3 density space at the B3LYP/6-31G** or 6-31G* level is used, the theoretical molecular density mol ( mol ϭ M/V, M is the molecular weight) is very close to the experimental crystal density cry .…”
Section: Methodsmentioning
confidence: 96%
“…Since Q and ρ are unknown for the unsynthesized hypothetical compounds, to predict their detonation properties, the modified K-J equations based on the calculation results of quantum chemistry were recommended [23,24,26,[38][39][40][41][42][43], in which the density of the explosive ρ was replaced by the crystal theoretical density (ρ c ) computed by the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…The empirical Kamlet-Jacobs equations [13] widely employed [2][3][4][14][15][16][17][18][19][20][21][22] to estimate the detonation velocity and detonation pressure, the important parameters reflecting the explosive performance of energetic materials were used: …”
Section: Computational Methods and Detailsmentioning
confidence: 99%